(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Intervertebral discs (IVDs) are key functional elements of the spinal column, providing it with flexibility, stability and cushioning. Their anatomical and physiological characteristics vary depending on the spine, which causes different clinical symptoms in degenerative changes. This article discusses the morphofunctional features of intervertebral discs of the cervical, thoracic and lumbar spine.